PEMBELAJARAN AQIDAH AKHLAK DENGAN STRATEGI INKUIRI UNTUK MEMBENTUK KARAKTER PESERTA DIDIK DI MADRASAH IBTIDAIYAH (MI) MUHAMMADIYAH TURUS KABUPATEN KLATEN - Diah Novita Fardani (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
Character education is a very important aspect in the current era of development. The purpose of this study is to shape the character of students from an early age. With the character that has been embedded in the students will fortify themselves from the dangers of future changes that will occur. This research was conducted with qualitative methods, data collection was done by observation and interview. The results of this research are that learning Aqidah Akhlak with inquiry strategies can shape the characteristics of students